Volume 1: Symposia 2015
DOI: 10.1115/ajkfluids2015-33780
|View full text |Cite
|
Sign up to set email alerts
|

Shut-Off Head Prediction in Single Stage Centrifugal Pumps

Abstract: The prediction of the performance characteristic in centrifugal pumps at flow rates other than the design flow is of high relevance but relatively uncertain. In the present study, an evaluation of the existing shut-off head prediction methods and an assessment of both, the empirical approach and the numerical simulation are performed. For this purpose, after a review of existing methodologies, the empirical predictions are compared against available statistical data for single stage volute pumps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As well known in many works, 3,4,34 the BPF and harmonic frequencies are generally observed when the impeller blades interact with the volute tongue. Indeed, in Figures 5–7, it is confirmed that the BPF of each case ( f /Ω = 4, 6, and 8) and its harmonic frequencies are observed for all the performance parameters.…”
Section: Resultsmentioning
confidence: 72%
“…As well known in many works, 3,4,34 the BPF and harmonic frequencies are generally observed when the impeller blades interact with the volute tongue. Indeed, in Figures 5–7, it is confirmed that the BPF of each case ( f /Ω = 4, 6, and 8) and its harmonic frequencies are observed for all the performance parameters.…”
Section: Resultsmentioning
confidence: 72%
“…6 For the conventional fuel centrifugal pump, the operating time at shut-off is so short that the temperature rise in the pump is small and can be neglected, so the problem of the temperature rise in a conventional centrifugal pump at shut-off has rarely been studied. To date, studies on the shut-off condition for a centrifugal pump have mainly focused on the shut-off head [7][8][9][10] and the shut-off power. 11 However, in the case of the afterburner fuel centrifugal pump, the problem of the high fuel temperature rise at shut-off cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%